2014
DOI: 10.1021/co500071x
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Structure–Property Relationship of p-Type Organic Semiconductors through Rapid Library Construction via a One-Pot, Suzuki–Miyaura Coupling Reaction

Abstract: The elucidation of the structure-property relationship is an important issue in the development of organic electronics. Combinatorial synthesis and the evaluation of systematically modified compounds is a powerful tool in the work of elucidating structure-property relationships. In this manuscript, D-π-A structure, 32 p-type organic semiconductors were rapidly synthesized via a one-pot, Suzuki-Miyaura coupling with subsequent Knoevenagel condensation. Evaluation of the solubility and photovoltaic properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The use of inorganic bases such as K 3 PO 4 and CaH 2 afforded a substantial amount of intermediate 3 (Entries 1 and 2). The optimization of the combination of catalysts and ligands (Entries [10][11][12] revealed that the combination of Pd(OAc) 2 / [(tBu 3 P)H]BF 4 afforded the best result (46 %), as shown in Entry 12. The use of toluene as a solvent was important.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The use of inorganic bases such as K 3 PO 4 and CaH 2 afforded a substantial amount of intermediate 3 (Entries 1 and 2). The optimization of the combination of catalysts and ligands (Entries [10][11][12] revealed that the combination of Pd(OAc) 2 / [(tBu 3 P)H]BF 4 afforded the best result (46 %), as shown in Entry 12. The use of toluene as a solvent was important.…”
Section: Resultsmentioning
confidence: 98%
“…More diluted conditions (0.125 m) resulted in a decrease of yield (Entry 3) and recovery of substrate 1. 2-Thio-phenecarbaldehydes are important structural components of dyes for dye-sensitized solar cells, [9b,9d,14] as well as for the use with drug candidates, [8c] and for use as organic ptype semiconductors, [10] because the aldehyde group offers opportunities for further chemical modifications. In this case, substrate 1 was recovered probably due to the slow oxidative addition of 1 to the Pd 0 species that was coordinated by multiple CO molecules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the longer term, our protocols could be further extended to provide a combinatorial-like approach to allow the rapid screening of the structure-property relationships of diverse libraries of dyes. 35,45 Interestingly, a comparison of device performance data of the three dyes shows that the N,N-dimethyaniline moiety produces devices with comparable efficiency to analogous sensitizers containing a N,N-dimethylaniline donor unit attached to the EDOT unit via an acetylene bridge or dyes containing more complicated indoline or triphenylamine donor units reported in the literature. 26,28,37 A substantial improvement in device performance (8.2%) was reported for a triphenylamine containing EDOT sensitizer but this is due to a modication of the acceptor unit in the dye.…”
Section: Discussionmentioning
confidence: 96%
“…[1][2][3][4] Traditionally, these carbon-hydrogen (C-H) DHA methods are catalyzed by soluble homogeneous palladium catalyst systems, which have the drawbacks of lower selectively, sensitivity to air, need for high temperature, and high-levels of residual palladium contamination in the resultant material. 5,6 In our group, we have recently reported on the synthesis of symmetrical small molecule-based semiconductors through a heterogeneous palladium (Pd) catalyzed DHA procedure.…”
mentioning
confidence: 99%